ANALYSIS OF Pb, Cu, and Zn METAL CONNECTIONS IN BLOOD SHELL MEAT (Anadara granosa) WITH DIFFERENT SIZES IN WATERS MUARA ASAHAN RIVER TANJUNGBALAI CITY NORTH SUMATERA - Syafri Syafri; Bintal Amin; Nursyirwani Nursyirwani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT  granosa.This research was conducted from January to April 2019 by taking samples of blood cockles from the waters of the Asahan river, Tanjungbalai city, North Sumatra Province. The purpuse of this research were to know the metal concentrations of Pb, Cu and Zn in different station and different sizes of blood cockle’s shell (Anadara granosa), as well as to find out the level of metal pollution based on MPI (Metal Pollution Index). Analysis of metal concentrations of heavy metal was done by following procedurs outline by Yap et al., (2003). The results showed that the highest Pb metal concentration in meat of small blood clams was found at station 3 namely, 0.7100 μg / g and the low concentration was 0.4716 μg / g at Station 1. While the highest concentration at medium size was found at Station 2 namely , 1.3683 μg / g and low concentration was 0.8000 μg / g at Station 1. The highest Pb concentration at large size was found at Station 3 ie, 2,2200 μg / g and the lowest concentration was 1,2266 μg / g at Station 1. The calculated MPI value for the Asahan estuary research from this study was 3,7260  which was considered quite low compared to other regions. Keywords: Heavy Metal, Pollution, North Sumatra, Industry, Anadara